Performance and carcass characteristics of three groups of crossbred steers fed to the same energy efficiency endpoint - Lipsey, R.J.; Dikeman, Michael E.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station, 2011)
Sixteen Maine Anjou and 16 Gelbvieh steer calves from Angus or Hereford crossbred dams, and 16 Hereford x Angus crossbred steers were fed the same ration in individual pens until they reached a weekly energy efficiency endpoint of 10.3 lb. of feed per pound of gain above their maintenance requirements.
Keywords: Beef; Performance; Carcass characteristics; Steers; Energy